2020
DOI: 10.1177/0267323120966849
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing exposure diversity

Abstract: The concept of exposure diversity, the diversity of information that people actually access and use, has recently gained prominence in media policy debates. This aspect of media diversity, however, remains difficult to define, measure or implement in actual policy. In this article, we propose an empirical approach that operationalizes exposure diversity in terms of news and current affairs providers in the media repertoire of different social groups. This can be studied through cluster analysis of survey data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
(56 reference statements)
0
7
0
1
Order By: Relevance
“…High-choice audiovisual media environments are not necessarily mirrored in people consuming a variety of content, but on the contrary, may increase the impact of content preferences (Prior, 2005). Our study, however, is not well suited to investigate exposure diversity, a field of research largely focused on the consequences of increased user choice for news consumption (Moe et al, 2020;Prior, 2005;Sjøvaag, 2016). Such enquiries require rigorous examinations of the same genres across media (Schrøder, 2015).…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…High-choice audiovisual media environments are not necessarily mirrored in people consuming a variety of content, but on the contrary, may increase the impact of content preferences (Prior, 2005). Our study, however, is not well suited to investigate exposure diversity, a field of research largely focused on the consequences of increased user choice for news consumption (Moe et al, 2020;Prior, 2005;Sjøvaag, 2016). Such enquiries require rigorous examinations of the same genres across media (Schrøder, 2015).…”
Section: Hypothesesmentioning
confidence: 99%
“…First, streaming services amplify contemporary high-choice media environments, situating media users in a position where they are free to follow their own content preferences (Prior, 2005). A concern for research has been how abundance and choice affect people's media consumption, including to what extent diversity in available content is reflected in exposure diversity (Moe et al, 2020;Prior, 2005;Sjøvaag, 2016). Yet, the idea that users are free to follow their content preferences needs to be critically considered, and increased user agency is a contested notion in critical research examining the structuring forces of streaming services.…”
Section: The Logics Of Streamingmentioning
confidence: 99%
“…The seminal news content homogeneity study of Bigman (1948) revealed that news stories in newspapers were often verbatim copies from one another. These studies form part of the normative deliberative democracy perspective that is recurring and dominant within relevant scholarship and emphasises dialogue between various viewpoints and the active duty of news media and a free press as a key aspect of democratic systems (Helberger et al, 2018; Masini et al, 2018; Moe et al, 2021; Papandrea, 2006; Raeijmaekers and Maeseele, 2015). Seen as a stepping stone towards achieving pluralistic societies, the concept of diversity within media markets and news content is typically foregrounded in academic and regulatory discussions as a key prerequisite, in spite of its definition and operationalisation remaining much-discussed yet still opaque (Hendrickx et al, 2020; Karppinen, 2013; Loecherbach et al, 2020; Sjøvaag, 2016).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It incorporated previous taxonomies such as internal and external diversity (McQuail and Van Cuilenburg, 1983) as well as vertical and horizontal diversity (Entman and Wildman, 1992: 11), which both relate to “the variety of ideas within a single media outlet”, and “the variety of ideas available across the aggregate of different media”, respectively. Simultaneously, Napoli’s multi-layered perspective of diversity served as the precursor for later classifications such as Helle Sjøvaag’s (2016) organisational, production, output and reception diversity and the expansion of the notion of structural diversity as “media ownership and the number of different outlets” (Moe et al, 2021: 1). The key discrepancy with the multidimensional news diversity model operationalised in the paper at hand is that it actively makes the case that the various components have an associative relationship and organically affect and alter one another: changes in the diversity of how news is produced will ultimately lead to alterations in the diversity of its output (e.g.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation